An evaluation method for determining the optimal structure of artificial reefs based on their flow field effects - Ma, Qiaofeng; Ding, Jian; Xi, Yanbin; Song, Jun; Liang, Shuxiu; Zhang, Ruijin (Frontiers in Marine Science, 2022)
To design artificial reef (ARs) structures that can provide better habitats for fish, extensive research has been conducted on the flow field effects of ARs with different structures. The evaluation indices of the flow field effects include upwelling and back vortex flow. However, there has been little quantitative analysis of these two indices. In addition, several studies have suggested that other flow field characteristics of ARs can aid in providing habitats for fish. To evaluate the flow field effects of ARs more comprehensively, the following work was conducted in this study. First, the flow field of the solid cubic AR was simulated using a computational fluid dynamics (CFD)-based software (Fluent), and based on the particle image velocimetry (PIV) approach, these simulation results were verified by flume experiments. Next, the flow fields of ARs with other structures (hollow cube, solid triangular pyramid, hollow triangular pyramid, solid truncated rectangular pyramid, and hollow truncated rectangular pyramid) were simulated using the verified numerical model. Subsequently, based on the analytic hierarchy process (AHP) approach, an evaluation model with six evaluation indices of the flow field effect of ARs (upwelling region, wake region, surface area of ARs, upper slow-flowing area, lateral slow-flowing area, and internal velocity of ARs) was established, and the weights of the evaluation indices were determined using the entropy weight method (EWM). Finally, to determine the structure of ARs with optimal flow field effects, the evaluation model was used for evaluating the flow field effects of all ARs. The superiority and ranking of the flow field effects of all ARs were calculated using the fuzzy comprehensive evaluation (FCE) method. This study provides a theoretical basis and reference for the optimization of AR structures.